Design of an enterprise architecture model for scientific publications based on ADM -TOGAF 9.0 - Saboya Ríos, Nemías (2018)
The objective of this research study was to design a proposed enterprise architecture model for scientific publications based on TOGAF 9.0 and modeling in Archimate for the Peruvian Union University (Universidad Peruana Unión). This is a technological study since it proposes a solution to the need to achieve positioning through an acceptable level of visibility for scientific publications according to established research fields.